Board leadership, board meeting frequency and firm performance in two-tier boards - Md Arafat Hossain; Elaine Yen Nee Oon (Managerial and Decision Economics, 2022)
We examine how board leadership influences the frequency of supervisory board meetings and how meeting frequency, in turn, affects firm performance. Utilizing a 10-year longitudinal dataset of German and Indonesian listed firms, we find that CEOs in both countries are more likely to foster lower board meeting frequency. However, in Germany, chairmen and female independent directors are more likely to promote higher board meeting frequency, while in Indonesia, affiliated directors and female independent directors have no significant influence. More frequent board meetings lead to better firm performance in Indonesia but not in Germany.
Keywords: C23; M14; G34; 330; Board meeting frequency; two-tier board structure; affiliated director; supervisory board; chairman; board leadership; firm performance; Germany; Indonesia